BALANCING TRADITION AND PUBLIC HEALTH: THE AL-SHAFI’I PERSPECTIVE ON FEMALE CIRCUMCISION IN LIGHT OF PP NO. 28/2024 AND MUI FATWA NO. 9A/2008 - Rambe, Sahri; Iwan (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2024)
This research examines the regulatory and religious perspectives on female circumcision in Indonesia, focusing on the interplay between Peraturan Pemerintah (PP) No. 28/2024 and Fatwa Majelis Ulama Indonesia (MUI) No. 9A/2008. The study aims to analyze the compatibility of these regulations with Islamic traditions, particularly the Shafi’i school of thought, and assess their implications for women’s rights and health. A qualitative comparative approach was employed, utilizing document analysis of the two regulations alongside relevant Islamic jurisprudential sources. Data were further contextualized through a normative-juridical framework, allowing for an in-depth exploration of religious, legal, and public health considerations. The findings reveal significant tensions between the two regulatory frameworks. While the MUI fatwa permits female circumcision within safe procedural limits and aligns with Shafi’i jurisprudence, PP No. 28/2024 emphasizes the protection of women’s physical and psychological health, categorizing female circumcision as potentially harmful. Both frameworks aim to safeguard women’s well-being, yet diverge in their application of this principle. This study contributes original insights by situating the debate within the broader discourse on the intersection of religion and modern regulatory systems in Indonesia. It highlights the need for a balanced approach that respects religious traditions while prioritizing women’s rights and health. The findings have significant implications for policymakers and religious leaders, suggesting the necessity of harmonizing religious practices with modern legal standards to address public health concerns and uphold human rights in a pluralistic society.